Anisotropic and high thermal conductivity in monolayer quasi-hexagonal fullerene: A comparative study against bulk phase fullerene. (1st June 2023) - Dong, Haikuan; Cao, Chenyang; Ying, Penghua; Fan, Zheyong; Qian, Ping; Su, Yanjing
Highlights: An accurate NEP model is developed to study heat transport of QHPF and BPF. Using the HNEMD method, we show that the k of QHPF is anisotropic. The inter-molecular bonding in QHPF can greatly enhance its k as compared to the BPF. Graphical abstract: Abstract: Recently a novel two-dimensional (2D) C 60 based crystal called quasi-hexagonal-phase fullerene (QHPF) has been fabricated and demonstrated to be a promising candidate for 2D electronic devices [Hou et al. Nature 606, 507–510 (2022)]. We construct an accurate and transferable machine-learned potential to study heat transport and related properties of this material, with a comparison to the face-centered-cubic bulk-phase fullerene (BPF). Using the homogeneous nonequilibrium molecular dynamics and the related spectral decomposition methods, we show that the thermal conductivity in QHPF is anisotropic, which is 137(7) W/mK at 300 K in the direction parallel to the cycloaddition bonds and 102(3) W/mK in the perpendicular in-plane direction. By contrast, the thermal conductivity in BPF is isotropic and is only 0.45(5) W/mK. We show that the inter-molecular covalent bonding in QHPF plays a crucial role in enhancing the thermal conductivity in QHPF as compared to that in BPF. The heat transport properties as characterized in this work will be useful for the application of QHPF as novel 2D electronic devices.